Respuesta :

Answer:

29 and 43

Step-by-step explanation:

1. Create two equations that represent the given information.

  • y - x = 14
  • y + x = 72

2. Use one of the equations to solve for one of the variables.

  • y - x = 14 can be rearranged algebraically to become y = 14 + x

3. Plug in the known variable (y = 14 + x) into the other equation.

  • We can replace the y in y + x = 72 with 14 + x, since y = 14 + x
  • Therefore, y + x = 72 turns into (14 + x) + x = 72

4. Solve for x algebraically.

  • (14 + x) + x = 72 ; get rid of the parenthesis
  • 14 + x + x = 72 ; add the x's together
  • 14 + 2x = 72 ; subtract 14 from both sides
  • 2x = 58 ; divide both sides by 2
  • x = 29

5. Now that we've solved for the exact value of x, we can plug that into our earlier equation where we solved for y.

  • y = 14 + x
  • y = 14 + 29 = 43

6. Our final answer is 29 and 43.

ACCESS MORE

Otras preguntas